The Diameter of a Zero-Divisor Graph for Finite Direct Product of Commutative Rings - Atani, S. Ebrahimi; Kohan, M. Shajari (Sarajevo Journal of Mathematics, 2024)
This paper establishes a set of theorems that describe the diameter of a zero-divisor graph for a finite direct product R_1× R_2×…× R_n with respect to the diameters of the zero-divisor graphs of R_1,R_2,…,R_n-1 and R_n(n>2). 2000 Mathematics Subject Classification. 05C75, 13A15